Short time dynamics in the isotropic phase of liquid crystals: the aspect ratio and the power law decay - Cang, Hu; Li, Jie; Fayer, M.D (Chemical physics letters, 2002)
Optical heterodyne detected optical Kerr effect (OHD-OKE) experiments are used to study the orientational dynamics of the liquid crystal 4 ′-octyl-4-biphenylcarbonitrile (8CB) in the isotropic phase near the isotropic to nematic phase transition. The results are compared to those for three other liquid crystals. The 8CB data display a short time scale temperature independent power law decay and a long time scale exponential decay with a temperature dependence described by Landau–de Gennes theory. The power law exponent is −0.56. Combining this result with previous results for three other liquid crystals [J. Chem. Phys. 116 (2002) 6339; J. Chem. Phys. 116 (2002) 360], it is found that the power law exponent depends linearly on the aspect ratio of the liquid crystal.